2019
DOI: 10.1371/journal.pone.0219600
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of permanent childhood hearing loss detected at the universal newborn hearing screen: Systematic review and meta-analysis

Abstract: Context Permanent childhood hearing loss (PCHL) can affect speech, language, and wider outcomes. Adverse effects are mitigated through universal newborn hearing screening (UNHS) and early intervention. Objective We undertook a systematic review and meta-analysis to estimate prevalence of UNHS-detected PCHL (bilateral loss ≥26 dB HL) and its variation by admission to neonatal intensive care unit (NICU). A secondary objective was to report UNHS programme performance (PROS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
52
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(72 citation statements)
references
References 58 publications
8
52
0
5
Order By: Relevance
“…Subsequently, the overall hearing loss adjusted prevalence with ABR rate was 0.64% (0.35% on one side, 0.29% on both sides). The prevalence of UNHS-detected hearing loss in highly developed countries is 0.11% 20 ; however, it is difficult to simply compare the prevalence of hearing loss because the definition of hearing loss and the diagnostic ABR rate varies by countries and papers. The government needs to make efforts to increase the ABR performing rate after an NHS test, not to fade the meaning of EHDI to help children with hearing loss.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, the overall hearing loss adjusted prevalence with ABR rate was 0.64% (0.35% on one side, 0.29% on both sides). The prevalence of UNHS-detected hearing loss in highly developed countries is 0.11% 20 ; however, it is difficult to simply compare the prevalence of hearing loss because the definition of hearing loss and the diagnostic ABR rate varies by countries and papers. The government needs to make efforts to increase the ABR performing rate after an NHS test, not to fade the meaning of EHDI to help children with hearing loss.…”
Section: Discussionmentioning
confidence: 99%
“…One in 1000 newborns are identified with severe to profound hearing loss at birth ( Butcher et al, 2019 ). Approximately 80% of prelingual deafness is due to genetic factors ( Marlin et al, 2005 ) with about a hundred identified gene abnormalities ( Ideura et al, 2019 , Bai et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Universal newborn hearing screening (UNHS) programs are potentially the best source of data on the prevalence of congenital deafness [4][5][6]. The rate of congenitally deaf infants is generally considered to vary from 1 to 3 per 1,000 newborns in developed countries and up to 24 per 1,000 newborns in developing countries due to the higher presence of risk factors [4][5][6][7][8][9]. Despite all benefits of the UNHS data, a very limited number of countries (mostly highly developed countries) have massively adopted such programs, and the reported rates of congenital deafness are not applicable for other parts of the world [4,7,9].…”
Section: Introductionmentioning
confidence: 99%
“…The rate of congenitally deaf infants is generally considered to vary from 1 to 3 per 1,000 newborns in developed countries and up to 24 per 1,000 newborns in developing countries due to the higher presence of risk factors [4][5][6][7][8][9]. Despite all benefits of the UNHS data, a very limited number of countries (mostly highly developed countries) have massively adopted such programs, and the reported rates of congenital deafness are not applicable for other parts of the world [4,7,9]. The lack of systematic reporting and analysis of data also greatly affects the correct evaluation of congenital HL prevalence by the UNHS [4,7,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation